HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU SEKSUAL REMAJA DI SMK N 1 DEPOK YOGYAKARTA - Putri Yunita Sari (Universitas Respati Yogyakarta, 2020)
Background: The effect which is caused by sexual behavior makes pregnance rate high for teenagers, abortion, and the transmission of various sexually transmitted diseases. Sexual behavior deviation by teenagers is caused by the condition of parenting especially parents in parenting their children. The introductory study on 5 student girls shows that two of them do sexual behaviors such as kissing on lips with their couple and they even touch their particular part of body ecah other, and one student only hold their couple’s hand only. Objective: To figure out the correlation between parenting formula and sexual behavior of teenagers in State Vocational School No.1 of Depok District Yogyakarta. Methods: This research uses analytical correlation method through cross sectional framework. Sampling technique uses purposive sampling with 89 respondents. The technique of data analysis uses Chi Square. Result : Mostly parenting formula is democratic formula shown by 88.8% of respondents. The teenagers’ sexual behavior deviation has good predicate shown by 91.0% of respondents. So that there is correlation between parenting formula and sexual behavior of teenagers with p-value = 0,000 and the correlation closeness is average shown by CC=0.491. Conclusion: consumption of GBR can reduce the risk of cardiovascular disease.